Cluster analysis of Sumatra Island earthquake distribution - Anggraini, Dian; Indratno, Sapto Wahyu; Mukhaiyar, Utriweni; Puspito, Antonius Nanang T. (Universitas Islam Negeri Raden Intan Lampung, 2024)
Sumatra Island is highly vulnerable to earthquakes due to multiple seismic sources, including megathrusts, faults, and volcanic activities spanning from Aceh to Lampung. The International Seismological Centre (ISC) has recorded 9,414 earthquakes in Sumatra with magnitudes ranging from 4.0 to 9.1 since 1907. Insufficient preparedness in responding to sudden earthquakes challenges local and central governments in managing impacts. To address this, a risk classification of earthquake-prone areas was conducted using cluster analysis. The